Enantioselective Cascade Biocatalysis via Epoxide Hydrolysis and Alcohol Oxidation: One-Pot Synthesis of (R)-?-Hydroxy Ketones from Meso- or Racemic Epoxides - Zhang, Jiandong (American Chemical Society, 2016)
ACS Catalysis